A Fluorescent Probe of Nitrite Based on Eu3+ Functionalized Metal‐Organic Frameworks. Issue 10 (6th April 2021) - Li, Yanping; Zhao, Yajun; Zhang, Wei; Shao, Kai; Zhou, Huizhong
Abstract: NO2 − sensing is closely associated with human health, and we adopted lanthanide Eu 3+ post‐modified MOF as NO2 − fluorescent probes. Typical stable MOF with uncoordinated carboxylic groups in the framework were chosen to encapsulate Eu 3+ . NO2 − could generate an obvious quenching response to the fluorescence intensity. This Eu 3+ functionalized MOF exhibited excellent fluorescence performances and obvious quenching response to NO2 − based on the energy transfer between Eu 3+ and NO2 − . This MOF based NO2 − fluorescent probe showed a highly splendid detection selectivity and sensitivity with a very low detection limit of 0.69 μM, which was significantly below the maximal level limits of NO2 − in drinking water set by the WHO. Abstract :